When opposites hurt: Similarity in getting ahead in leader-follower dyads as a predictor of job performance evaluations - Laura Guillén; Natalia Karelaia (European School of Management and Technology (ESMT), 2012)
Status-seeking behaviors are linked to executive career progression, but do leaders appreciate being surrounded by followers eager to move up in the organizational hierarchy? Building on the self-enhancement theory, we propose that leaders with high self-assessed getting-ahead behaviors give better performance evaluations to subordinates who also have willingness to get ahead behaviors. In contrast, leaders with low self-assessed getting-ahead behaviors are quite reserved about the performance of subordinates high in the getting-ahead dimension. We also propose that overall, ambitious leaders evaluate more positively their followers' performance than leaders with more modest desire to get ahead. We suggest that this effect is magnified when the status differential between the leader and the follower is reduced due to differences in age or hierarchical level (i.e., a younger leader or too few hierarchical levels between the leader and the subordinate). The results obtained by using polynomial regression and response surface techniques to analyze a sample of 138 leader-follower dyads supported our hypotheses showing a supervisor's contextual performance ratings skew rooted in leaders' desire to get ahead. We conclude by deriving the theoretical and practical implications of these findings.
urn:nbn:de:101:1-201307224200
Keywords: 650; getting-ahead similarity; leader-follower dyads; job performance evaluation; self-enhancement; 360-degree instruments; Führungskräfte; Persönlichkeitspsychologie; Selbstorganisation; Selbstevaluation; Personalkontrolle; Leistungsbeurteilung; Verhalten in Organisationen